Chemometric-Guided Exploration of Marine Anti-Neurofibroma Leads - Chen, Lo-Yun; Peng, Bo-Rong; Lai, Guan-Yi; Weng, Hao-Jui; El-Shazly, Mohamed; Su, Chun-Han; Su, Jui-Hsin; Sung, Ping-Jyun; Liao, Chung-Ping; Lai, Kuei-Hung (Frontiers in Marine Science, 2022)
In-depth analysis of metabolomics diversity of marine species through advanced mass spectrometric analysis is one of the most promising new tools for the development of marine drugs against mild and life-threatening diseases. Neurofibromas are a common type of tumor in the peripheral nervous system. Currently, there are very limited treatment options for neurofibromas. In our course of exploring potential therapeutic agents for neurofibroma treatment, the multi-informative molecular networking (MIMN) approach was proposed. The MIMNs of the Lendenfeldia sp. sponge extract and sub-fractions were established according to their inhibitory activity against several inflammatory chemokines (CCL3, CCL4, CCL5, CXCL1, CXCL8, and CXCL10) in neurofibroma cell line hTERT-NF1-ipNF95.11b-C (CRL-3390). The visualized MIMN revealed the anti-inflammatory potential of scalarane-enriched fractions, and the follow-up annotation and isolation led to the identification of a scalarane, 24-methyl-12,24,25-trioxoscalar-16-en-22-oic acid (2). Our results revealed that the most abundant scalarane (2) dominated the anti-chemokine effect of Lendenfeldia sp. extract together with other scalaranes, indicating the potential application of sponge-derived scalaranes to be developed as therapeutic agents for neurofibromas.